2011
DOI: 10.5005/jp-journals-10020-1008
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy does not Cure Bevacizumab Induced Uveitis

Abstract: Non-infectious inflammation associated with intravitreal antivascular endothelial growth factor injections has been reported recently. Failure to recognize this sterile inflammation can result in unnecessary treatment for endophthalmitis.We describe a case of acute noninfective intraocular inflammation following the third intravitreal injection of bevacizumab for nonischemic central retinal vein occlusion-associated cystoid macular edema in a 74-year-old man who responded temporarily to repeated intravitreal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…We have found that vitrectomy does not cure bevacizumab induced vitritis and the vitreous inflammation persists until the bound anti-VEGF agent is eliminated from the eye, which may take 6 weeks or longer. 10 Bevacizumab induced vitritis responds to systemic steroids and this would be the preferred initial treatment in this patient. Intravitreal antibiotics are not necessary and intravitreal steroid is an alternate option to systemic steroid, provided the patient does not have elevated intraocular pressure.…”
Section: How Would One Manage the Patient Furthermentioning
confidence: 91%
“…We have found that vitrectomy does not cure bevacizumab induced vitritis and the vitreous inflammation persists until the bound anti-VEGF agent is eliminated from the eye, which may take 6 weeks or longer. 10 Bevacizumab induced vitritis responds to systemic steroids and this would be the preferred initial treatment in this patient. Intravitreal antibiotics are not necessary and intravitreal steroid is an alternate option to systemic steroid, provided the patient does not have elevated intraocular pressure.…”
Section: How Would One Manage the Patient Furthermentioning
confidence: 91%